Association Between Obesity and the Trends of Routes of Hysterectomy Performed for Benign Indications. Issue 4 (April 2015) - Mikhail, Emad; Miladinovic, Branko; Velanovich, Vic; Finan, Michael A.; Hart, Stuart; Imudia, Anthony N.
Abstract : OBJECTIVE: To estimate the association between obesity and the recent trends of routes chosen for hysterectomy performed for benign indications in the United States. MATERIALS AND METHODS: Using the American College of Surgeons–National Surgical Quality Improvement Project's database, patients who underwent hysterectomy for benign indications from 2005 to 2011 were identified by International Classification of Diseases, 9th Revision codes and were categorized into total abdominal hysterectomy (TAH), total vaginal hysterectomy (TVH), laparoscopically assisted vaginal hysterectomy (LAVH), and total laparoscopic hysterectomy (TLH). The patients were divided into four subgroups according to body mass index (BMI) (less than 25, 25–29.9, 30–39.9, and 40 or greater). The data were analyzed using Student's t test or χ 2 and Fisher's exact test. RESULTS: A total of 18, 810 patients underwent hysterectomy for benign indications during the study period: 9, 852 (52.4%) were TAH, 5, 146 (27.4%) TVH, 2, 296 (12.2%) LAVH, and 1, 516 (8.0%) TLH. The rates of TAH increased from 45.7% in patients with ideal body weight to 62% in morbidly obese patients ( P <.001). The rate of TVH and LAVH decreased from 32.7% and 13.3% in patients with ideal body weight to 17.1% and 11.7% in morbidly obese patients, respectively ( P <.001 and 0.04). The rate of TLH performed was independent of BMI ( P =.61). Higher BMI was associated with longer operative time ( P <.001) in all routes of hysterectomy. The rates of superficial and deep wound infections were higher with increasing BMI in patients undergoing TAH ( P <.001) but not with TVH ( P =.26), LAVH ( P =1.0), or TLH ( P =.48). CONCLUSION: Regarding hysterectomy performed for benign indications, increasing BMI was associated with increased rate of TAH and decreased rate of TVH and LAVH, but not the rate of TLH. Increasing BMI was associated with increased operative time for all subgroups and increased surgical site infection in the TAH group. LEVEL OF EVIDENCE: II Abstract : Increasing obesity is associated with an increased rate of abdominal hysterectomy and a decreased rate of vaginal hysterectomy but has no association with the rate of total laparoscopic hysterectomy.